2015
DOI: 10.1017/s0950268815002368
|View full text |Cite
|
Sign up to set email alerts
|

One Health approach to controlling a Q fever outbreak on an Australian goat farm

Abstract: SUMMARYA recent outbreak of Q fever was linked to an intensive goat and sheep dairy farm in Victoria, Australia, 2012-2014. Seventeen employees and one family member were confirmed with Q fever over a 28-month period, including two culture-positive cases. The outbreak investigation and management involved a One Health approach with representation from human, animal, environmental and public health. Seroprevalence in non-pregnant milking goats was 15% [95% confidence interval (CI) 7–27]; active infection was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 38 publications
2
89
0
Order By: Relevance
“…Although a direct link between the human C. burnetii cases previously reported in the study region, and the C. burnetii seropositive domestic small ruminants in the current study could not be established, there is a plausible zoonotic public health risk link of animal to human transmission which may need further investigation (Chang et al., ; Dean et al., ; De Lange et al., ; Bond et al., ).…”
Section: Discussionmentioning
confidence: 66%
“…Although a direct link between the human C. burnetii cases previously reported in the study region, and the C. burnetii seropositive domestic small ruminants in the current study could not be established, there is a plausible zoonotic public health risk link of animal to human transmission which may need further investigation (Chang et al., ; Dean et al., ; De Lange et al., ; Bond et al., ).…”
Section: Discussionmentioning
confidence: 66%
“…All procedures performed in studies involving animals were in accordance with the ethical standards of the University of Melbourne [University of Melbourne Animal Ethics Committee approval number 1413118].) The herd had previously tested positive for C. burnetii antibodies in serum using CFT testing and had also tested positive for C. burnetii DNA in air samples, vaginal swabs, and placenta samples using PCR (42). There were also 22 laboratory-confirmed human cases of acute Q fever associated with the farm (42).…”
Section: Methodsmentioning
confidence: 99%
“…The herd had previously tested positive for C. burnetii antibodies in serum using CFT testing and had also tested positive for C. burnetii DNA in air samples, vaginal swabs, and placenta samples using PCR (42). There were also 22 laboratory-confirmed human cases of acute Q fever associated with the farm (42). Two-fold serial dilutions of the serum samples, from 1:40 to 1:40,960, were prepared and tested in duplicate using the IFA to determine the endpoint titer above which no antibodies to C. burnetii were detected in each of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of research in Australia tends to focus on analysis of notified cases (35), unusual outbreaks, (36, 37), or animal and environmental sources (38). However, a recent study by Bond et al (39) demonstrated the application and outcomes of taking a One Health approach to an outbreak associated with a goat farm. The outbreak investigation and its management involved a team representing animal, environmental, and public health professionals.…”
Section: Resultsmentioning
confidence: 99%
“…The outbreak investigation and its management involved a team representing animal, environmental, and public health professionals. Activities included serological and molecular studies to characterise transmission followed by an evaluation of farming practices to identify points of intervention (39). An intensive human vaccination programme plus environmental and biosecurity interventions was credited with resolving the outbreak (39).…”
Section: Resultsmentioning
confidence: 99%